PENGARUH PELATIHAN KERJA, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V KEBUN AIR MOLEK 1 - , Arwinance Pramdewi, Lili Purwanti ,Rosnelly Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of training and work discipline on the performance of PT. Perkebunan Nusantara V Air Molek 1 . The population of this research is all employees of PT. Perkebunan Nusantara V Air Molek 1 has 94 employees. For data collection, the method used is the Questionnaire method (Questionary) which is a list of statements about training, work discipline and employee performance. The questionnaire in this study used statements developed from indicators of training, work discipline and employee performance. This study uses multiple linear regression analysis using SPSS (Statistical Package of Social Science). The results of the study based on the partial t test showed that job training obtained t count (2.498) > t table (1.992) with a significance value of 0.015 <0.05. meaning that job training has a positive and significant effect on employee performance. Work discipline obtained t count (4.941) > t table (1.992) with a significance value of 0.000 <0.05. means that work discipline has a positive and significant effect on employee performance. Furthermore, based on the simultaneous F test shows job training, work discipline jointly affect employee performance with an F count of 19.994 and a significance of 0.000.Keywords: Training, Work Discipline, Employee Performance.